Sleep disturbance in caregivers of individuals with Parkinsonism: a systematic review and meta-analysis. Issue 11 (15th November 2022) - Sprajcer, Madeline; Owen, Patrick J; Crowther, Meagan E; Harper, Kirsty; Gupta, Charlotte Cecelia; Ferguson, Sally A; Gibson, Rosemary H; Vincent, Grace E
Abstract : Objectives: The global prevalence of Parkinsonism continues to rise given ageing populations. Individuals with Parkinsonism who have moderate or severe symptoms typically require a high level of care, including assistance with activities of daily living. This care is often provided across the 24-hour period by a family member or friend. It is likely that providing care significantly impacts the sleep duration and quality of the caregiver given overnight caring responsibilities, in addition to worry and stress associated with the caregiving role. The aim of this systematic review and meta-analysis was to investigate whether providing care to an individual with Parkinsonism was associated with disturbed caregiver sleep, and to identify associated factors that may contribute to disturbed sleep in this population. Setting: Five databases were electronically searched on 30 June 2021 including CINAHL, PubMed, PsycINFO, CENTRAL and EMBASE. Participants: Eligibility criteria included a population of caregivers whose care recipient has a form of Parkinsonism. Primary and secondary outcome measures: To be included in this systematic review, outcome measures of caregiver sleep (eg, sleep duration, sleep quality) were required. Results: Eighteen studies (n=1998) were included. Findings indicated that caregivers of individuals with Parkinsonism typically experience poor sleep quality (mean (95% CI): 5.6 (4.8 to 6.4) points on the Pittsburgh Sleep Quality Index), increased sleep latency and poor sleep efficiency. Conclusions: The degree of poor sleep quality was clinically significant. However, further investigation of sleep outcomes is required using sleep measurement tools tailored for this population (eg, measures that capture overnight sleep disruption by care recipient/s). Additionally, there is a need for appropriate individual and societal-level interventions to improve caregiver sleep. PROSPERO registration number: CRD42021274529.